Implementasi Rencana Strategis Pengembangan Obyek Wisata Unggulan Taman Wisata Alam Kawah Ijen (Studi Di Dinas Kebudayaan Dan Pariwisata Kabupaten Banyuwangi) - Putri, Immas Sahaya (Jurnal Administrasi Publik, 2015)
Abstract: Implementation of the Strategic Plan for Development of Featured Destinations Nature Park of Ijen Crater (Studies in the Department of Culture and Tourism Banyuwangi). Banyuwangi is one area in Indonesia has three leading tourist attraction, one of the Natural Park of Ijen Crater. The charm of natural beauty of Ijen Crater that is able to attract tourists is also supported by the efforts of the Department of Culture and Tourism in developing infrastructure and tourism promotion, through policies Strategic Plan of Culture and Tourism 2010-2015. The method used in this research is descriptive research with qualitative approach. The results showed that the crater development efforts such as improved accessibility, development of facilities Tourist Information Center, human resource development, and tourism promotion through collaboration between agencies and tourism entrepreneurs. In maximizing the development of the Natural Park of Ijen Crater required active role of stakeholders and an adequate budget so that activities can be carried out with the optimal development. Keywords: tourism development, the Department of Culture and Tourism Strategic Plan District Banyuwangi years 2010-2015 Abstrak: Implementasi Rencana Strategis Pengembangan Obyek Wisata Unggulan Taman Wisata Alam Kawah Ijen (Studi di Dinas Kebudayaan dan Pariwisata Kabupaten Banyuwangi). Kabupaten Banyuwangi merupakan salah satu daerah di Indonesia memiliki tiga obyek wisata unggulan, salah satunya TWA Kawah Ijen. Pesona keindahan alam TWA Kawah Ijen yang mampu memikat wisatawan turut didukung oleh upaya Dispar Kabupaten Banyuwangi dalam mengembangkan sarana dan prasarana serta promosi wisata, melalui kebijakan Renstra Dispar tahun 2010-2015. Hasil penelitian menunjukkan bahwa upaya pengembangan Kawah Ijen seperti perbaikan aksesbilitas, pembangunan sarana Tourist Information Center, pembinaan sumber daya manusia, serta promosi wisata melalui kerjasama antara instansi dan pengusaha pariwisata. Dalam memaksimalkan pengembangan TWA Kawah Ijen diperlukan peran aktif stakeholder dan anggaran yang memadai agar kegiatan pengembangan dapat dilaksanakan dengan optimal. Kata kunci: pengembangan pariwisata, Renstra Dinas Kebudayaan dan Pariwisata Kabupaten Banyuwangi tahun 2010-2015